Health-related quality of life in children aged 8-12 years with thalassemia: a cross-sectional study using the pediatric quality of life inventory PedsQL - Nadgir, Akshata; Wajapey, Pallavi; Samaja, Y. Sai Sudha; S. K., Ramya (International Journal of Research in Medical Sciences, 2026)
Background: Thalassemia is a chronic hereditary hemoglobinopathy characterized by defective hemoglobin synthesis, resulting in lifelong anaemia and dependence on regular blood transfusions and iron chelation therapy. The prolonged treatment burden, frequent hospital visits, and associated physical and psychosocial challenges can significantly impair the quality of life (QoL) of affected children. Assessment of QoL is essential to understand the multidimensional impact of the disease beyond clinical parameters and to support holistic, patient-centred care. Methods: A cross-sectional study was conducted among 40 children aged 8-12 years diagnosed with thalassemia and attending Samraksha- Thalassemia Day Care Centre, Bengaluru. Quality of life was assessed using the parent-proxy version of the pediatric quality of life inventory (PedsQL) 4.0 generic core scales, which evaluates physical, emotional, social, and school functioning. Demographic and anthropometric data were recorded. Descriptive statistics were used, and associations between overall QoL scores and gender, age, height, weight, and body mass index were analysed using appropriate statistical tests. Results: Quality of life was compromised across all domains. The lowest median scores were observed in physical functioning (median: 3; IQR: 2-5) and social functioning (median: 3; IQR: 1-4). The median overall QoL score was 14.5 (IQR: 11-20.25). Male children demonstrated significantly higher overall QoL scores compared to female children (p=0.024). Conclusions: Children with thalassemia experience significant impairments in multiple domains of quality of life, emphasizing the need for comprehensive multidisciplinary management.